Evaluating the impact of continuous venovenous hemodiafiltration on the efficacy of prophylactic fondaparinux doses: a prospective single-center observational study - Aleksander Aszkiełowicz; Karol P. Steckiewicz; Radosław Owczuk (Scientific Reports)
Abstract Critically ill patients often need continuous renal replacement therapy (CRRT). This process can remove particles as large as 10 kDa, including medications such as fondaparinux. In this study, we investigated whether patients who received prophylactic doses of fondaparinux and are treated with continuous veno-venous hemodiafiltration (CVVHDF) would achieve prophylactic levels of anti-Xa factor activity. In this observational study, we compared two groups of patients: 20 individuals who underwent CVVHDF and 20 individuals who did not undergo CVVHDF. Each patient received a prophylactic subcutaneous dose of 2.5 mg daily of fondaparinux. Anti-Xa factor activity was measured on the third day of treatment with fondaparinux. Blood samples were collected at four time points: immediately before the administration of fondaparinux and then 3, 6, and 9 h later. Anti-Xa factor activity levels were below the recommended range in the control group and in most CVVHDF patients but significantly increased after fondaparinux administration. Interestingly, individuals who underwent CVVHDF had greater anti-Xa factor activity than control patients did at several time points. In critically ill patients treated with prophylactic fondaparinux, CVVHDF appears to have a statistically significant but small effect on Xa factor activity. However, the clinical significance of this finding is unknown. Clinical Trial Registration: The study was prospectively registered at ClinialTrials.gov (NCT04671160).